2012
DOI: 10.1093/icvts/ivs199
|View full text |Cite
|
Sign up to set email alerts
|

Primary mucoepidermoid carcinoma of the trachea in a child

Abstract: Mucoepidermoid carcinoma of the trachea is a rare tumour, especially in the paediatric population. We report the case of a 9-year-old boy with mucoepidermoid carcinoma of the trachea that was preoperatively diagnosed as an intraluminal polypoid mass arising from the trachea and extending into the right main bronchus. A complete resection of the tumour with reconstruction and end-to-end anastomosis of the trachea was performed. The patient is now, 24 months after surgery, free of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…Review of case reports of mucoepidermoid carcinoma of the trachea or bronchi in all ages suggests that definitive treatment is surgical resection . In this patient, we demonstrated that operative planning of definitive resection can be augmented with high‐frequency radial‐probe endobronchial ultrasound, which has a resolution approaching 100 microns and can distinguish the multilayer structure of the tracheobronchial wall.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Review of case reports of mucoepidermoid carcinoma of the trachea or bronchi in all ages suggests that definitive treatment is surgical resection . In this patient, we demonstrated that operative planning of definitive resection can be augmented with high‐frequency radial‐probe endobronchial ultrasound, which has a resolution approaching 100 microns and can distinguish the multilayer structure of the tracheobronchial wall.…”
Section: Discussionmentioning
confidence: 81%
“…Diagnosis of tracheal mucoepidermoid carcinoma remains a challenge, and review of the literature suggests that there is a delay of several months between symptom onset and tumor identification. Most often, initial symptoms are attributed to asthma, and further radiographic and endoscopic workup is only initiated after lack of response to inhaler therapy …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less than 10 children with tracheal MEC have been reported in literature. [ 3 8 ] This article describes a 12-year-old boy with wheezing and a history of asthma who was finally diagnosed with MEC at the carina of trachea after an initial misdiagnosis of asthma. To our knowledge, this is the first case of tracheal tumor with coexisting asthma.…”
Section: Introductionmentioning
confidence: 99%